Atypical trigeminal neuralgia: role of neurophysiological tests for diagnosis - Carmelo Costa; Domenico Restivo; Antongiulio Bruschetta (Publiediting, 2023)
Trigeminal neuralgia is a common condition among the adult population. Its diagnosis is primarily clinical and simple enough in typical cases featuring brief, electric-shock like paroxysmal pain triggered by harmless gestures within the trigeminal nerve territory. Laboratory and imaging tests are not available to confirm its occurrence. In addition to the paroxysmal pain forms, there are also other atypical forms featuring continuous background pain between paroxysms. In these cases, differential diagnosis with other neuropathic and non-neuropathic facial pain can be challenging. Trunk functional tests, such as the blink reflex, have been shown in some circumstances to be decisive in arriving at a correct diagnosis, as in the clinical case we present.